Kesiapan Mental Atlet Atletik Kabupaten Banjarnegara Dalam Menghadapi Event Student Athletic Championship (SAC) Central Java - Feriska Amelia Putri; Donny Wira Yudha Kusuma; Ranu Baskora Aji Putra; Roas Irsyada (Indonesian Journal for Physical Education and Sport, 2024)
The Athletic Team in Banjarnegara Regency in facing the Central Java Students Athletic Championship (SAC) event has not been known the level of mental readiness because this is an international event that has only been held for the last two seasons. Mental Readiness is the most important thing in an athlete's performance in a match. Thus the purpose of this study is to determine the mental readiness of athletes in terms of motivation, self-confidence, anxiety and concentration. This study is a quantitative study with a survey design. The research analysis uses statistical analysis and descriptive exploration methods. The results of the analysis of the Mental Readiness of Athletic Athletes in Facing the Central Java Student Athletic Championship (SAC) Event are in the "high" category. This study is limited to the factors of motivation, self-confidence, anxiety and concentration. It is hoped that further research can add other psychological aspects. The conclusion of the results of this study is that the supporting factors in the mental readiness of athletic athletes include motivation factors in the "very high" category, self-confidence factors in the "high" category, anxiety factors in the "sufficient" category, and concentration factors in the "high" category. Suggestions in this study are that coaches must always monitor the mental readiness of athletes in every training to face a championship